Cisternal trochlear nerve schwannoma: improvement of diplopia after subtotal tumour excision - Younes, Walid M.; Hermann, Elvis Josef; Krauss, Joachim K. (British journal of neurosurgery, 2012)
Objective and importance. Trochlear nerve schwannomas without neurofibromatosis are very rare. No more than 33 cases have been pathologically verified. None of the reported cases showed postoperative improvement of trochlear palsy. The authors present a case of trochlear palsy due to a trochlear nerve schwannoma with subsequent improvement of trochlear palsy after subtotal excision of the tumour. Clinical presentation. A 65-year-old woman presented with diplopia, vertigo and left arm weakness. There was no history of neurofibromatosis. MR imaging demonstrated a tumour in the right perimesencephalic/ambient cistern. Intervention. The tumour was operated by a pterional approach, and subtotal excision was achieved preserving the tumour capsule with the trochlear nerve. The tumour was pathologically diagnosed as a schwannoma. Conclusion. At 2-year follow-up, there was no double vision and MR imaging showed a small, stable tumour remnant. To our knowledge, this is the first reported case of a trochlear schwannoma in whom postoperative improvement of trochlear function was achieved.